Intronic PRRT2 mutation generates novel splice acceptor site and causes paroxysmal kinesigenic dyskinesia with infantile convulsions (PKD/IC) in a three generation family. Issue 1 (December 2016) - Weber, Axel; Kreth, Jonas; Müller, Ulrich
Abstract Background Mutations inPRRT2 cause autosomal dominant paroxysmal kinesigenic dyskinesia with infantile convulsions (PKD/IC). Case presentation A previously not recognized intronicPRRT2 mutation (c.880-35G > A; p.S294Lfs *29) was found in an 18 month old girl with IC and in her mother with classical presentation of PKD. The mutation results in a novel splice acceptor site in intron 2 ofPRRT2 . Due to frameshift and a subsequent premature stop-codon the resulting transcript appears to render the PRRT2 protein non/dysfunctional and is the likely cause of disease in this family. Conclusion Our findings expand the mutational spectrum of this disease.